Stability, delay, and chaotic behavior in a Lotka-Volterra predator-prey system - S. Nakaoka; Y. Saito; Y. Takeuchi (Mathematical Biosciences and Engineering)
We consider the following Lotka-Volterra predator-prey system with two delays:$x'(t) = x(t) [r_1 - ax(t- \tau_1) - by(t)]$$y'(t) = y(t) [-r_2 + cx(t) - dy(t- \tau_2)]$ (E)We show that a positive equilibrium of system (E) is globally asymptotically stable for small delays. Critical values of time delay through which system (E) undergoes a Hopf bifurcation are analytically determined. Some numerical simulations suggest an existence of subcritical Hopf bifurcation near the critical values of time delay. Further system (E) exhibits some chaotic behavior when $tau_2$ becomes large.